(NmEDX (B/s - (NpOD^AJNOWA(B, (NwASSA nIKOLAEWNAs; (NsIMONOWA(B, (NlEONORA nIKOLAEWNAs; (NpQTNICKIJ(B, (Ni(B.(Nw(B.s ((NmOSKWA (B:s (NnAUKA(B,s, 1990)
(NpREDM(B. (NUKAZ(B.: (NS(B. 274-276s
(NbIBLIOGR(B.: (NS(B. 227-273 (2020 (NNAZW(B.)s
Keywords: (NmEDX (B- (NhIMI^ESKIJ ANALIZs